Phytochemical and Antimicrobial Studies of Strychnos wallichiana Steud Ex Dc - M.N. Radhamma, P.B. Mallikharjuna, Y.N. Seetharam (Journal of Phytology, 2010)
A preliminary phytochemical screening of seed and leaf of Strychnos wallichiana, an Asiatic woody liana species belongs to the family Loganiaceae revealed the presence of alkaloids, phenols, glycosides, flavonoids, saponins and sterols. Further, the HPLC chromatogram of alkaloid profile of seed has shown twelve prominent alkaloid peaks. Furthermore, the methanol and aqueous extracts were evaluated for in vitro antimicrobial properties against the selected bacteria and fungi at the concentration 2 mg/ml and 4 mg/ml, respectively using agar well diffusion assay. The findings have revealed considerable to significant inhibition activity of pathogens tested.